Adsorptive therapy as a modificator for tumor-host interaction - Sakhno, L.A.; Sarnatskaya, V.V.; Yushko, L.A.; Snezhkova, E.A.; Bardakhivskaya, K.I.; Shevchuk, O.O.; Sidorenko, A.S.; Nikolaev , V.G. (PH Akademperiodyka, 2023)
Summary. The potential of one of the adsorption methods, enterosorption (ES), using the new generation of carbon adsorbents to correct the negative manifestations of tumor-host interaction in the framework of paraneoplastic syndrome (PNS) as well as systemic toxicity of chemo- and radiation therapy, is discussed. The ES influence on the development of PNS was demonstrated in C57/BL6 mice with transplanted Lewis lung carcinoma. Two-week administration of carbon enterosorbents resulted in a significant suppression of metastasis and correction of tumor-related anemia, activation of granulocytic line in the bone marrow with nearly 3-fold enhancement of its mitotic activity. ES exerted a positive influence on the structural-morphologic indexes and regenerative potential of kidneys and liver, mitigated manifestations of oxidative stress, decreased the level of endogenous intoxication, increased resistance of erythrocyte membranes and decreased ligand loading of blood plasma transport proteins. The effect of ES on anticancer activity and toxic reactions of cisplatin (CP) was evaluated in Guerin carcinoma-bearing rats. ES reduced significantly creatinine and other kidney biochemical indexes elevated in the blood plasma of rats after CP treatment. ES attenuated dystrophic changes in the histological structure of internal organs (kidney, liver, spleen), caused by tumor growth and significantly aggravated under the influence of CP. Such changes were specially traced in the kidneys and well reflect the nephroprotective potential of ES. In rats irradiated with X-ray in sublethal dose, highly activated granulated carbonic enterosorbents facilitated the restoration of white blood cells and lymphocyte count. The results obtained confirm the insights of academician R.E. Kavetsky predicting the future of adsorptive detoxification with activated carbons in the treatment of cancer patients.